Islamic Legal Pluralism and Localized Ijtihad in Rural Indonesia: Negotiating Madhhab, Custom, and Multicultural Muslim Life - Aziz, M Abd; Ghony, Muhammad Djunaidi; Suprayogo, Imam; Amin, Mukhlisah (Mazahibuna: Jurnal Perbandingan Mazhab, 2026)
This ethnographic study examines how Islamic law is contextually reinterpreted within multicultural rural Muslim communities in Indonesia through negotiations between dominant Shāfiʿī doctrines, local customs, and plural legal reasoning. Focusing on Nganget Hamlet, East Java, the study addresses a gap in contemporary madhhab studies by exploring how everyday Muslim communities selectively appropriate cross-madhhab principles beyond formal juristic institutions. Using participant observation, in-depth interviews, and document analysis, the findings reveal three interrelated dynamics. First, inheritance disputes are commonly resolved through musyawarah-mufakat (deliberative consensus), reflecting a shift from rigid farāʾiḍ (Islamic inheritance rules) formulations toward maṣlaḥah (public benefit)-oriented reasoning that draws upon juristic flexibility recognized across Sunni madhhab traditions. Second, local rituals such as sedekah bumi (earth thanksgiving ritual) and ruwatan desa (village purification ritual) are legitimized as ʿurf ṣaḥīḥ (valid customary practice) through maqāṣid al-sharīʿa (objectives of Islamic law) considerations, demonstrating how customary practices are accommodated within Islamic legal interpretation. Third, informal Islamic education functions as a space for transmitting pluralistic legal understandings in which multiple madhhab perspectives are pragmatically negotiated in everyday life. The study argues that Islamic law in rural multicultural contexts operates as a dynamic form of localized ijtihad (independent legal reasoning) that continuously negotiates between normative Shāfiʿī authority and socio-cultural realities.  This research contributes to debates on legal pluralism and comparative madhhab studies by positioning Fiqh Nusantara as an applied model of cross-madhhab adaptability grounded in maqāṣid (higher objectives of Islamic law), ʿurf (customary practice), and lived Islamic legal practice in Southeast Asia.